Sustainable Analysis of Small Rivers with a Case Study in Poland - Czarneck,; Dr. Adam Czarnecki,; R.R.,; Lewandowska-Czarnecka, (Global Journal of Human-Social Science, 2014)
The present study represents a methodological research of environment factors and anthropic perturbation related with small rivers in the Vistula Mouth in Poland The aim of this study is to assess the potential of environment services in one study area with a particular environment characterized by the small rivers The methodology used is based on field expeditions and review of the literature In this work it was analysed the concept of rebuild connections between small rivers and local society In particular this work relates how to achieve an environment with better interaction with local society it was performed an analysis of possibilities to carry out actions to maintain preserve or rehabilitate the small rivers The results of the study shows the importance of the small rivers as reported in this paper make some recommendations for further interaction between small rivers and local society